EXPERIMENTAL DETERMINATION OF THE INDUSTRIAL APPLICATION AND DETERMINATION EFFICIENCY OF FLUID GASES CLEANING APPARATUS BY CONTACT ELEMENT METHOD - Ergashev Nasimbek Akhmadjonovich; Isomidinov Azizjon Salomidinovich; Madaliyev Akhrorbek Niyzomidin ogli; Xomidov Xushnudbek.Rapiqjon ogli; Ovloyorov Xaydarali Аliyorovich (American Journals Publishing, 2022)
The article recommends the industrial application of a wet dust collection and gas cleaning device with a contact element sliding motion and to determine its cleaning efficiency.
Keywords: consumption, rolling flow, wet method, contact element, rolling motion, liquid film, dolomite dust, air flow, gas flow